Effect of Stem Cell-Derived Extracellular Vesicles on Damaged Human Corneal Endothelial Cells. (18th January 2021) - Nuzzi, Raffaele; Buono, Lola; Scalabrin, Simona; De Iuliis, Marco; Bussolati, Benedetta
Abstract : Purpose . Human corneal endothelial cells (HCECs) are essential to visual function; however, since they have limited proliferative capacity in vivo, they are prone to corneal endothelial dysfunction. At present, the only treatment is a corneal transplantation from donor cadavers. Also, due to a global shortage of donor corneas, it is important to find alternative strategies. Recent studies highlight that stem cell–derived extracellular vesicles (EVs) play a relevant role in stem cell-induced regeneration by reprogramming injured cells and inducing proregenerative pathways. The aim of this work is to evaluate whether EVs derived from mesenchymal stem cells (MSC-EVs) are able to promote regeneration of damaged HCECs. Methods . We isolated HCECs from discarded corneas in patients undergoing corneal transplantation or enucleation (N = 23 patients). Bone marrow mesenchymal stem cells (MSCs) were obtained from Lonza, cultured, and characterized. MSC-EVs were obtained from supernatants of MSCs. In order to establish a valid in vitro damage model to test the regenerative potential of EVs on HCECs, we evaluated the proliferation rate and the apoptosis after exposing the cells to serum-deprived medium at different concentrations for 24 hours. We then evaluated the HCEC migration through a wound healing assay. Results . In the selected serum deprivation damage conditions, the treatment with different doses of MSC-EVs resulted in a significantly higher proliferation rate of HCECs at all the tested concentrations of EVs (5 ‐ 20 × 10 3 MSC-EV/cell). MSC-EVs/cell induced a significant decrease in number of total apoptotic cells after 24 hours of serum deprivation. Finally, the wound healing assay showed a significantly faster repair of the wound after HCEC treatment with MSC-EVs. Conclusions . Results highlight the already well-known proregenerative potential of MSC-EVs in a totally new biological model, the endothelium of the cornea. MSC-EVs, indeed, induced proliferation and survival of HCECs, promoting the migration of HCECs in vitro .